Image Compression with Embedded Multiwavelet Coding - Liang, Kai-Chieh; Li, Jin; Kuo, C.-C. Jay (1996)
An embedded image coding scheme using the multiwavelet transform and inter-subband prediction is proposed in this research. The new proposed coding scheme consists of the following building components: GHM multiwavelet transform, prediction across subbands, successive approximation quantization, and adaptive binary arithmetic coding. Our major contribution is the introduction of a set of prediction rules to fully exploit the correlations between multiwavelet coefficients in different frequency bands. The performance of the proposed new method is comparable to that of state-of-the-art wavelet compression methods.